Integrated algorithm based on vectors in node localization for wireless sensor networks - WANG Yu-feng; WANG Yan (Tongxin xuebao)
An integrated algorithm based on DV-hop was designed and applied to mobile nodes. A location correction vector（LCV）was constructed by the differences between estimated distances and range measurements; an improved particle swarm optimization （PSO） was used to find correction steps of nodes; location correction equaled the value of LCV multiplying step. The algorithm and its complexity and validity had been approved through simulation,the results show that the localization error of DV-hop has been reduced by 75% using the algorithm, and it is also applicable to low-density networks.